2020
DOI: 10.3389/fphar.2020.561306
|View full text |Cite
|
Sign up to set email alerts
|

Ubc9 Attenuates Myocardial Ischemic Injury Through Accelerating Autophagic Flux

Abstract: Aims: SUMOylation is a post-translational modification that plays a crucial role in the cellular stress response. We aimed to demonstrate whether and how the SUMO E2 conjugation enzyme Ubc9 affects acute myocardial ischemic (MI) injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Increasing evidence has shown that bafilomycin A1 could hinder the degradation of p62 25,26 and potentially elevate LC3 B accumulation. 27,28 These were consistent with the results above. Therefore, p62 degradation was inhibited in SGC-7901 and SGC-7901/DDP cells, indicating that bafilomycin A1 had suppressed cell autophagy effectively.…”
Section: ■ Resultssupporting
confidence: 92%
“…Increasing evidence has shown that bafilomycin A1 could hinder the degradation of p62 25,26 and potentially elevate LC3 B accumulation. 27,28 These were consistent with the results above. Therefore, p62 degradation was inhibited in SGC-7901 and SGC-7901/DDP cells, indicating that bafilomycin A1 had suppressed cell autophagy effectively.…”
Section: ■ Resultssupporting
confidence: 92%
“…81 Ubc9 levels were increased after myocardium ischemia in mice, and the administration of a Ubc9-expressing adenovirus directly to the infarct area of the heart, to further increase Ubc9 levels in the damaged area, reduced cardiomyocyte apoptosis and fibrosis, and improved cardiac function. 71 This improvement was also attributed to the enhancement of the autophagic influx, which facilitates cell restoration against starvation and other stresses. 84 Xiao et al 71 reported that although the basal levels of Vps34, a member of Class III phosphatidylinositol 3-kinase (PI3K) that regulates cell homeostasis and autophagy, did not change, SUMOylation seemed to regulate the interaction of Vps34 and other factors, such as Beclin1, which enhance the autophagic influx.…”
Section: Heartmentioning
confidence: 99%
“…71 This improvement was also attributed to the enhancement of the autophagic influx, which facilitates cell restoration against starvation and other stresses. 84 Xiao et al 71 reported that although the basal levels of Vps34, a member of Class III phosphatidylinositol 3-kinase (PI3K) that regulates cell homeostasis and autophagy, did not change, SUMOylation seemed to regulate the interaction of Vps34 and other factors, such as Beclin1, which enhance the autophagic influx. Bian et al 70 demonstrated that ischemia/reperfusion injury reduced SUMOylated proteins and Ubc9 expression; however, supplementation with zinc prevented Ubc9 decrease, improved the SUMO1-ylation of DRP-1induced mitophagy, enhanced damaged mitochondrial clearance, and decreased ROS.…”
Section: Heartmentioning
confidence: 99%
“…AML cells transfected with the SUMOylation motif of IGF-1R mutants (K1025A and K1100A) result in decreased cell proliferation by IGF-1 [ 141 ]. Ubiquitin conjugating enzyme 9 (UBC9) is a SUMO E2-conjugation enzyme and plays a critical role in SUMOylation [ 142 ]. Inhibition of UBC9 using an anti-UBC9 antibody reduces the expressions of IGF-1R and SUMO-1, with subsequent inhibition of cell proliferation [ 141 ].…”
Section: Sumoylation In Amlmentioning
confidence: 99%
“…This inhibitory effect promotes apoptosis but does not affect the differentiation of APL cells [ 167 ]. Conversely, upregulated UBP43 expression stabilizes PML/RARα protein and inhibits apoptosis [ 142 ].…”
Section: Deisgylation In Amlmentioning
confidence: 99%